Oestrus induction and fertility response in post-partum anoestrus dairy cows treated with homeopathic medicine - T SATHYABAMA; T ALAGU MANIVANNAN; K RAJAMANICKAM; A KIRUBAKARAN (Indian Journal of Animal Sciences, 2024)
The study was carried out to evaluate the effect of two homeopathic medicines to induce oestrus in 36 postpartum anoestrus crossbred Jersey dairy cows. Group 1 cows were fed a mineral mixture, and group 2 and 3 were medicated with Pulsatilla and Sepia drenched at the dose rate of 20 mL twice daily for 8 days, respectively. The mean plasma progesterone level (ng/mL) estimated using a radio immunoassay kit was significantly higher in group 2, followed by group 3 before and after medication on day 28 and 60, post artificial insemination (AI). Out of 12 induced for oestrus, 10 cows (83.33 %) and 9 cows (75.0 %) in group 2 and 3 were confirmed pregnant by rectal palpation on day 60 post AI, respectively. Both the homeopathic medicines showed 100% oestrus induction with a mean interval of 25.17 to 25.50 days, and Pulsatilla medicated cows showed improved fertility response than Sepia. The significantly higher level of progesterone after the withdrawal of homeopathic medication might be due to the release of circulating hormone, which blocks estradiol negative feedback. The subsequent increase reduces uterine PGF2 alpha secretion for a better conception rate.